2022
DOI: 10.3389/fendo.2022.994898
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin and vasoinhibin are endogenous players in diabetic retinopathy revisited

Abstract: Diabetic retinopathy (DR) and diabetic macular edema (DME) are major causes for visual loss in adults. Nearly half of the world’s population with diabetes has some degree of DR, and DME is a major cause of visual impairment in these patients. Severe vision loss occurs because of tractional retinal detachment due to retinal neovascularization, but the most common cause of moderate vision loss occurs in DME where excessive vascular permeability leads to the exudation and accumulation of extracellular fluid and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…The cleavage of PRL occurs at the hypothalamus, the pituitary gland, and the target tissue levels, defining the PRL/vasoinhibin axis ( 30 ). This axis contributes to the physiological restriction of blood vessels in ocular ( 31 , 32 ) and joint ( 26 ) tissues and is disrupted in angiogenesis-related diseases, including diabetic retinopathy ( 33 ), retinopathy of prematurity ( 34 ), peripartum cardiomyopathy ( 35 ), preeclampsia ( 36 ), and inflammatory arthritis ( 37 ). Furthermore, 2 clinical trials have addressed vasoinhibin levels as targets of therapeutic interventions ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cleavage of PRL occurs at the hypothalamus, the pituitary gland, and the target tissue levels, defining the PRL/vasoinhibin axis ( 30 ). This axis contributes to the physiological restriction of blood vessels in ocular ( 31 , 32 ) and joint ( 26 ) tissues and is disrupted in angiogenesis-related diseases, including diabetic retinopathy ( 33 ), retinopathy of prematurity ( 34 ), peripartum cardiomyopathy ( 35 ), preeclampsia ( 36 ), and inflammatory arthritis ( 37 ). Furthermore, 2 clinical trials have addressed vasoinhibin levels as targets of therapeutic interventions ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cleavage of PRL occurs at the hypothalamus, the pituitary gland, and the target tissue levels defining the PRL/vasoinhibin axis (30). This axis contributes to the physiological restriction of blood vessels in ocular (31,32) and joint (26) tissues and is disrupted in angiogenesis-related diseases, including diabetic retinopathy (33), retinopathy of prematurity (34), peripartum cardiomyopathy (35), preeclampsia (36), and inflammatory arthritis (37). Furthermore, two clinical trials have addressed vasoinhibin levels as targets of therapeutic interventions (38).…”
Section: Discussionmentioning
confidence: 99%
“…11 Microvascular complications that also include retinopathy and disturbances in neural sheath microvasculature are frequently found in patients with diabetes, even before their HbA1c is detoriated. 12 In a prior study, we showed that prolactin induces phosphorylation of ERK1/2 and STAT5 and induces tube formation of endothelial cells on Matrigel. These effects are blocked by a specific prolactin receptor antagonists, del1-9-G129R-hPRL.…”
mentioning
confidence: 92%